2017
DOI: 10.1021/acs.iecr.6b04181
|View full text |Cite
|
Sign up to set email alerts
|

Uranium Adsorption Tests of Amidoxime-Based Ultrahigh Molecular Weight Polyethylene Fibers in Simulated Seawater and Natural Coastal Marine Seawater from Different Locations

Abstract: Uranium recovery from seawater was investigated in simulated seawater in the laboratory and in natural seawater from the coasts of China with different amidoximebased (AO) ultrahigh molecular weight polyethylene (UHMWPE) fibers. The capacities of adsorbents AO-UHMWPE-1 and -2 were 4.54 and 2.41 mg U/g-adsorbent, respectively, after 24 h of adsorption in the simulated seawater with 330 ppb U. Their capacities were 2.93 and 1.95 mg U/gadsorbent, respectively, after 42 days of adsorption in simulated seawater flo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Table 2 shows the initial concentrations of various metal ions in simulated seawater, whose pH was adjusted to ∼8.1 by anhydrous Na 2 CO 3 . 5 The sorbent (0.1 g) was immersed into 5 L of simulated seawater, shook at 25 °C and 100 rpm for 24 h. The sorbent was then washed with deionized water and dried at 60 °C overnight under a vacuum. Specific details of determination for adsorption capacity were described in a previous work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 shows the initial concentrations of various metal ions in simulated seawater, whose pH was adjusted to ∼8.1 by anhydrous Na 2 CO 3 . 5 The sorbent (0.1 g) was immersed into 5 L of simulated seawater, shook at 25 °C and 100 rpm for 24 h. The sorbent was then washed with deionized water and dried at 60 °C overnight under a vacuum. Specific details of determination for adsorption capacity were described in a previous work.…”
Section: Methodsmentioning
confidence: 99%
“… 3 , 4 As is well known, the mixed water-organic solvents, e.g. , H 2 O/methanol (CH 3 OH) and H 2 O/dimethyl sulfoxide (DMSO), are usually used as the amidoximation solvent; 2 , 5 7 moreover, the mass of the organic solvent is usually dozens or even hundreds of times that of the sorbent. 2 , 8 This obviously increases the production cost of the sorbent and imposes potential environmental risks in a scale-up production.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, fibers (e.g. nylon textiles) have been employed as carriers of amidoxime groups in uranium harvest from seawater due to good mechanical strength, cheapness, and versatile utilization forms (Sugasaka et al 1981;Ling et al 2017;Tseng et al 2009;Zhang et al 2010). Additionally, the newly developed porous crystals, metal-organic frameworks (Li et al 2018;Liu et al 2017) and covalent organic frameworks (Sun et al 2018), are also studied as porous decorating platforms for the grafting of amidoxime groups.…”
Section: Adsorptionmentioning
confidence: 99%
“…To explore the reasons, abound works were preformed, which reported that open-chain AO and cyclic imide dioxime groups co-form during the amidoximation process and cyclic imide dioxime groups are more efficient in complexing U(VI) than open-chain AO under marine environment. 11,12 Rao et al 13,14 reported that three derivatives of AO, including glutarimidoxioxime (HL III , closed-ring), glutarimidedioxime (H 2 L I , closed-ring) and glutardiamidoxime (H 2 L II , open-ring), are present in PAO. These derivatives have very different complex capabilities with U(VI), and only H 2 L I can effectively bond to U(VI) against the competition of carbonate [15][16][17] and vanadium 18 in seawater.…”
Section: Introductionmentioning
confidence: 99%